A comparison of using the DSM-5 and MABC-2 for estimating the developmental coordination disorder prevalence in Korean children. (November 2019) - Lee, Kyujin; Jung, Taeyou; Lee, Do Kyeong; Lim, Jae-Chun; Lee, Eunbi; Jung, Youngok; Lee, Yongho
Highlights: The estimates of DCD prevalence based on the DSM-5 and MABC-2 were not different. The prevalence of high-risk DCD in Korean children is similar to other countries. Mild-risk DCD prevalence in Korean children is inconsistent with figures previously reported in other countries. Abstract: Background: Previous literature has shown inconsistency in the prevalence of developmental coordination disorder (DCD). The Movement Assessment Battery for Children, Second Edition (MABC-2) is often used for DCD prevalence studies, although the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) recommends four criteria. Aims: The purpose of this study was to compare the prevalence of DCD in Korean children using the DSM-5 and MABC-2. Methods: A total of 548 Korean elementary school students (mean age: 8.5 years ± 4.5 months) completed this study procedure. All four criteria defined by the DSM-5 were used to classify children with DCD. MABC-2 test scores were used to classify students into four subgroups: high-risk DCD, mild-risk DCD, probable DCD and typical development. Results: Cohen's kappa revealed that the estimates of DCD prevalence were not significantly different between MABC-2 and DSM-5. When DSM-5 criteria were applied, 60 children out of 548 were classified as probable DCD (10.94%) compared to 70 children with probable DCD (12.77%) when MABC-2 was used. Conclusions: DCD prevalence based on DSM-5 is not significantly different from MABC-2, though it tends to estimate less than MABC-2. Future studies should consider our findings when selecting an assessment tool.